Implementação de unidade de processo para geração de energia empregando vinhaça e integração na biorrefinaria de produção de etanol - Longati, Andreza Aparecida (2018)
The biofuels production is a promising alternative for decreasing fossil fuels dependency globally. Great efforts have been made in the search for energy optimization of the biofuel production process, in order to improve its sustainability and productivity. In Brazilian biorefineries sugar, ethanol, and electricity are produced from sugarcane. However, a considerable fraction of the energy from sugarcane (as organic matter) remains in vinasse. The anaerobic digestion (AD) of vinasse is a promising alternative, since it allows the recovery of energy (as biogas) while promote the reduction of its polluting organic load. In this context, the aim of this work was to evaluate different scenarios for the use of the biogas produced from vinasse in the AD of sugarcane vinasse. Also the biorefinery concept in the sugar-energy sector is introduced. First, it was used the Retro-Techno Economic Analysis (RTEA) approach. It consists of choosing the most important variables of the process and finding their threshold values and the correlation between them. The methodology was able to identify the main variables that affect the process global economic performance: enzyme load in the cellulose hydrolysis reactor, cellulose-to-glucose, and xylose-to-ethanol yields. Windows of feasible operation are the graphical output of the methodology, outlining regions to be further explored experimentally. Then, the biogas production from the vinasse in AD plants was investigated. Single- and two-phase AD systems were evaluated using technical, economic, and environmental aspects. It was assessed the use of biogas as a source of energy for the cogeneration system and as an energy source in an bagasse industrial dryer. The results showed that the AD system with two-phase presented higher biogas production for both biorefineries, 1G and 1G2G, resulting in higher eletricity production in both cases. In addition, in the 1G2G processes, the surplus energy provided by the use of biogas allowed more bagasse to be diverted to the 2G ethanol production, increasing the process productivity. The methodology identified the main variables that affect the process global economic performance of the AD plants: hidraulic retention time, conversion and the CH4 fraction in the biogas for the AD plants with single-phase. For AD plants with two-phase system the variables were: hidraulic retention time of the reactors (acidogenic and methanogenic) and biogas yield. The use of the biogas as an energy source of the bagasse dryer presented economic positive results in wide ranges of variation. In the environmental assessment, the use of biogas showed a smooth decrease in the environmental impacts compared to the conventional process and the 1G2G process presented the better results for most of environmental impacts categories compared to the 1G process. The results indicate that the use of biogas is a promising technology. Its production and use is responsible for improving the productivity and environmental impacts of the plant.